Strategi Komunikasi Pemasaran Dalam implementasi Program Co-Branding Desa Berdikari LAZWAF Al Azhar bersama (DEKS) Bank Indonesia - Matali, Lias (Universitas Al Azhar Indonesia, 2024)
An advanced village is a village that minimizes poverty to become an independent village from its communities, even though the poverty rate in Indonesia has decreased it is not optimal in dealing with it. There is an effort to advance the development and development of the village from the backwardness in governance and increased income of the local economy to the prosperity of the community, it is a necessary and appropriate strategy to create public confidence in the facility of cooperation of all parties that can make a concept and carry out the implementation of the program of village jointly. Institutions/Stakeholders striving to create a self-reliant village and have sustainable empowerment need a communication strategy with the role of the Zakat fund. The Berdikari Village Program is a concept-built Co-branding Program between LAZWAF AL Azhar and the Ministry of Economy and Finance of Shariah Bank Indonesia. This research uses a qualitative methodology approach with focused data collection, in-depth interviews, and literacy studies. This research focuses on the marketing communication strategy carried out by LAZWAF Al Azhar with the main theoretical foundation of persuasive communication. The results of this research in realizing the implementation of the program Village Berdikari successfully carried out the institution and became insight into the community's and other agencies' knowledge in using effective Communication strategy to co-brand a joint program..Keywords: Co-Branding, Empowerment of Community, Marketing Communication Strategy